2014
DOI: 10.1523/jneurosci.1137-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Ablation of Astroglial CCL2 Suppresses CNS Accumulation of M1 Macrophages and Preserves Axons in Mice with MOG Peptide EAE

Abstract: Current multiple sclerosis (MS) therapies only partially prevent chronically worsening neurological deficits, which are largely attributable to progressive loss of CNS axons. Prior studies of experimental autoimmune encephalomyelitis (EAE) induced in C57BL/6 mice by immunization with myelin oligodendrocyte glycoprotein peptide 35-55 (MOG peptide), a model of MS, documented continued axon loss for months after acute CNS inflammatory infiltrates had subsided, and massive astroglial induction of CCL2 (MCP-1), a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 84 publications
4
73
0
1
Order By: Relevance
“…Therefore, the receptor Mas may be an interesting therapeutic target to treat autoimmune diseases via regulating inflammatory processes. A specific activation of Mas, e.g., via agonists like AVE 0991, may impair macrophage migration through the BBB or in the vessel wall, thus limiting inflammation in the CNS or the vascular system (28,34,35). (B and C) In ApoEKO mice, Mas deficiency leads to increased oxidative stress measured by urinary 8-isoprostane and aortic nitrotyrosine expression levels (measurements were repeated for a total of three times; n = 6-8, *P < 0.05, mean ± SEM).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the receptor Mas may be an interesting therapeutic target to treat autoimmune diseases via regulating inflammatory processes. A specific activation of Mas, e.g., via agonists like AVE 0991, may impair macrophage migration through the BBB or in the vessel wall, thus limiting inflammation in the CNS or the vascular system (28,34,35). (B and C) In ApoEKO mice, Mas deficiency leads to increased oxidative stress measured by urinary 8-isoprostane and aortic nitrotyrosine expression levels (measurements were repeated for a total of three times; n = 6-8, *P < 0.05, mean ± SEM).…”
Section: Discussionmentioning
confidence: 99%
“…Those T cells that are present in the circulating cerebral spinal fluid under homeostatic conditions are enriched for memory T cell markers and CXCR3 expression (111); however, a role for specific receptors in T cell immune surveillance of the CNS has not been defined. The atypical structure of the CNS parenchyma under homeostatic conditions may require distinct mechanisms of T cell interstitial motility from those utilized by T cells recruited to the CNS by inflammation and infection (112).…”
Section: Unique Lanscape Of the Cnsmentioning
confidence: 99%
“…Third, the combination of the presence of kynurenine metabolites and TRP depletion increases the number of regulatory T cells positive for forkhead box P3 (FOXP3 + ) via TGFβ induction and its impact on naive T cells (110). Moreover, downstream TRP catabolites are able to shift dendritic cells to a tolerogenic phenotype independent of the microenvironment TRP levels, i.e., without functional IDO-1 (111,112). Therefore, IDO-1 competent dendritic cells also contribute to KP-mediated immune-suppression by contributing to a tolerogenic environment.…”
Section: Kp Influence On the Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Perivascular and parenchymal foamy macrophages do not express CCL2 protein and are likely to contribute to resolution of inflammation by inhibiting further lesion development and promoting lesion repair [13,14]. On this line of evidence it has recently been reported that in a murine model of experimental autoimmune encephalomyelitis, mice with conditional astroglial ablation of CCL2 showed a reduced severity of pathology due to less spinal cord axonal loss [15] (Moreno et al 2014).…”
Section: Ms Is An Inflammatory Disease Of the Central Nervous System mentioning
confidence: 99%